The economy as an issue in the Middle Eastern press - Procházka-Eisl, Gisela; Strohmeier, Martin (Neue Beihefte zur Wiener Zeitschrift für die Kunde des Morgenlandes, 2008)
This volume comprises papers delivered at the sixth meeting of the conference series "History of The Press in the Middle East" which was held in Nicosia/Cyprus from 19 to May 23, 2004. The meeting was devoted to the theme "The Economy as an Issue in the Middle Eastern Press"